2009
DOI: 10.1007/s11224-009-9540-y
|View full text |Cite
|
Sign up to set email alerts
|

The role of symmetry in building up zeolite frameworks from layered zeolite precursors having ferrierite and CAS layers

Abstract: Layered zeolite precursors represent an emerging class of materials that expand the zeolite field in a new direction and have already produced new intriguing discoveries. One is a new fundamental insight that a zeolite framework can assemble by two pathways, directly in 3-D and via a layered precursor. Also new types of materials such as pillared and delaminated zeolites have been synthesized. Starting with the discovery of MCM-22 precursor in 1990s, other framework structures have now been obtained by topotac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…Due to its close structural relationship with CDO zeolite, the FER framework topology has been identified in a number of 2D layered precursors (Table 4 and 2D layer precursors of CDO in Table 2). The differences between the crystal structure among these related 2D FER precursors result from the stacking sequence of FER layers, i.e., the displacement of layers parallel to the a-b plane and/or interlayer distance [136], which is the consequence of incorporating different templates in syntheses. Among these FER precursors, the most prominent ones are PREFER, PLS-3, ICP (Instituto de Catálisis y Petroleoquímica)-2 and ERS (EniRicerche molecular Sieve)-12 (Table 4).…”
Section: D Layers With Fer Framework Topologymentioning
confidence: 99%
“…Due to its close structural relationship with CDO zeolite, the FER framework topology has been identified in a number of 2D layered precursors (Table 4 and 2D layer precursors of CDO in Table 2). The differences between the crystal structure among these related 2D FER precursors result from the stacking sequence of FER layers, i.e., the displacement of layers parallel to the a-b plane and/or interlayer distance [136], which is the consequence of incorporating different templates in syntheses. Among these FER precursors, the most prominent ones are PREFER, PLS-3, ICP (Instituto de Catálisis y Petroleoquímica)-2 and ERS (EniRicerche molecular Sieve)-12 (Table 4).…”
Section: D Layers With Fer Framework Topologymentioning
confidence: 99%
“…In the organization phase the lamellae could be arranged in many ways -different relative positions of lamellae can lead to topologically different zeolites or disordered products. Although preparation of multiple zeolites by lamellae rearrangements was not achieved by ADOR yet, this possibility can be illustrated on the FER and CDO zeolites formed by different arrangements of the same lamellae [7]. After rearrangement the FER-type material was prepared from CDO precursor RUB-36 [8], however, a combination of swelling and deswelling and the use of a suitable SDA was necessary.…”
Section: Introductionmentioning
confidence: 99%
“…In the paper by Roth and Dorset [107], it is shown that the symmetry principles may govern and rationalize formation of different zeolite frameworks from corresponding layered zeolite precursors. Despite their seeming complexity as defined by the large number of atoms per formula unit, enthalpies of formation of zeolites are encouragingly wellunderstood [108].…”
Section: Issuementioning
confidence: 99%